WIRAUSAHA DAN KREATIFITAS MEMBUAT SNACKS IN HAND PADA REMAJA DI BANDAR LAMPUNG - Rina Milyati Yuniastuti; Jhon Nasyaroeka; Maria Kristiningsih (Institut Informatika dan Bisnis Darmajaya, 2023)
This community service is carried out with the aim of creating entrepreneurship for young women in particular and developing and honing youth creativity. The training focuses on making in-hand snacks in the form of a funnel design. The funnel design is a funnel-shaped design covered in transparent plastic and filled with various kinds of snacks. Making this funnel design is simpler and cheaper. Cheap in the sense that if it is realized in entrepreneurship, the price will be affordable if it is bought and sold. The training was attended by young women with the method of providing material and direct practice. Services were given to young women at RT 03 LK 1 Bandar Lampung. The difficulty found in this service is the lack of creative youth in making snack designs in hand and in mixing and matching snacks as fillings. It is hoped that in this service young women will be creative in making designs and a creative spirit has begun to emerge and can already mix and match various forms of snacks.Keywords: Snack in hand, Funnel, Entrepreneurship, Creativity